Recovery Identity and Wellbeing: Is It Better to be 'Recovered' or 'in Recovery'?. Issue 1 (2nd January 2017) - Best, David; Andersson, Catrin; Irving, Jamie; Edwards, Michael
ABSTRACT: Although there has been debate about the meaning of recovery, there has been little discussion about how people characterize their own recovery experience, in particular whether people describe themselves as recovered (as with a therapeutic community [TC] philosophy) or as in recovery (typically those engaged in 12-step). The article assesses differences in wellbeing as a function of recovery self-ascriptions, based on the UK Life in Recovery survey. Those who described themselves as recovered or ex-addicts reported better psychological health and lower identification with addicts and recovery and showed stronger recovery functioning. There are clearly multiple pathways to recovery, and philosophy may impact on both trajectory of recovery and the social identity mechanisms underpinning change.